Nilai-Nilai Moral dalam Film Pinocchio (1940) Karya Disney: Analisis Moral - Enrico Andhika Pratama (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to analyze the moral values represented in the Pinocchio film produced by Walt Disney Animation Studios. The research focuses on moral values portrayed through dialogues, visual symbols, conflicts, and character development throughout the story. This study employed a qualitative descriptive method with a narrative analysis approach. The data were collected through audiovisual observation and documentation of important scenes related to moral values in the film. The analysis used the moral values theory proposed by Thomas Lickona as the grand theory, supported by children’s literature theory from Burhan Nurgiyantoro and the concept of moral imagination by Vigen Guroian. The results show that the film represents four main moral values: honesty, responsibility, courage, and sacrifice. These values are depicted through Pinocchio’s moral journey from a naïve wooden puppet into a “real boy.” The study concludes that Pinocchio (1940) is not only an entertainment medium but also an effective visual children’s literature work in conveying moral messages that remain relevant to contemporary audiences.